Antropologia visual, práticas antigas e novas perspectivas de investigação - Ribeiro, José da Silva (Revista de Antropologia, 2005)
The visual anthropology was Born in the mid-XIX century with the "age of technical reproduction" and the industrial expansion. How can one reformulates today, in the age of globalization and digital transformation, this discipline or disciplinary convergence? Having been initially focused on the documentation and preservation of endangered cultural practices, an anthropology of urgency, how it eventually mutated in visual, sound, audiovisual narrative forms, and, more recently, digital forms? Originally focused on feeding and enriching the museum's collections, how it is transmitted today by means of multiple forms and media to the public space in its search for new spectators/actors (or audiences)? First an instrumentation that apparently granted it an objective view, allocating to itself the status of research technology or even an assistant of research, how did it confronted or anticipated itself to new epistemological paradigms? Oriented above all for the recording of the ritual and material techniques and, after that, for words and sounds, how does it orients itself today in the scope of new objects of study as the anthropology of art, the anthropology of design, visual culture in contexts of accelerated social and cultural transformation processes? We add two more questions to the unrest that makes as reflect on this theme: how can one rethink today visual anthropology regarding anthropology per se? What it is one to do with visual anthropology today? We will seek to draw some ways of ancient practices that are gaining a new, better importance in this day and age (the work with archives, memory, the relation between past and project, the objects, the material culture) and put new opportunities, new practices, new objects of study into perspective.